Assessment of hydrological response with an integrated approach of climate, land, and water for sustainable water resources in the Khari River basin, India. (March 2023) - Mundetia, Nitika; Sharma, Devesh; Sharma, Aditya; Dubey, Swatantra Kumar; Mitra, Bijon K.; Dasgupta, Rajarshi; Jeong, Hanseok
Abstract: Lack of integrated approaches in the assessment of land, water, and climate-related problems leads to the development of ineffective solutions at the country level. It put further challenges to achieve regional-level sustainable development targets. This is particularly true for countries like India where water, land, and climate problems are very complex and interconnected starting from the watershed level to the regional level. Interlinked synergies work as the key to achieving collective action to target multiple sustainable development goals (SDG). The land, water, and climate components are prioritized in SDG 6, 13, and 15 goals respectively, which are assessed through an integrated approach using a Soil and Water Assessment Tool (SWAT) model. A semi-arid ungauged Khari basin is selected for the sustainability assessment and hydrologic response study. As the region is critical in terms of shortage of water, land conversions, and climate change and can present a way to address challenges in regional-level sustainability assessments. SWAT model is considered for two land-use scenarios, 1990 and 2015, for the period 1990–2019 and two climate scenarios, Representative Concentrated Pathways (RCP 4.5 and RCP 8.5), for the period 2021–2050 while keeping the slope and soil data same in both models. The simulated discharge data matched well with the observed discharge data, with NSE of 0.72, PBIAS of − 1.9, R 2 of 0.72 during calibration, and NSE of 0.72, PBIAS of − 4.7, and R 2 of 0.73 during validation. It can be observed from the Land use change scenario assessment that an increase in the fallow agriculture land area shows a positive relation with surface runoff and a negative relation with percolation. Similarly, climate change scenario assessment shows that in future scenarios temperature will increase in both the RCPs 4.5 and 8.5 but hydrological components are more responsive to the changes in rainfall than temperature changes. Study results pointed out that both land use change and climate change can significantly affect the surface as well as groundwater availability of the region and it also highlights the functionality of an integrated assessment approach that assesses land, water, and climate components of SDGs through a hydrological model. It supplies an understanding of important interlinked influences and responses that are to be studied and managed collectively at the regional level in future studies.